2019
DOI: 10.1039/c9mt00067d
|View full text |Cite
|
Sign up to set email alerts
|

The pivotal role of MBD4–ATP7B in the human Cu(i) excretion path as revealed by EPR experiments and all-atom simulations

Abstract: Atox1–MBD4 interaction mediates the in-cell Cu(i) concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 51 publications
8
48
2
Order By: Relevance
“…Since the dynamics of a spin label bound to the C41 (C41R1) of Atox1 is relatively high, the only explanation for this is that when spin-labeled Atox1 interacts with MBD1-3 and MBD4-6, the dynamics of C41R1 is reduced, meaning that Atox1 is trapped between the various MBDs. This is in agreement with our previous findings [23], where we suggested that the Atox1 monomer interacts with MBD3-4 only in a face-to-face manner with MBD4, and that it is not affected by the presence of MBD3. Here, the dynamics of the spin-labeled C41R1 position of Atox1 are not affected and not reduced, since there is no other MBD nearby.…”
Section: Probing the Interaction Between The Mbds Of Atp7b And The Mesupporting
confidence: 94%
See 4 more Smart Citations
“…Since the dynamics of a spin label bound to the C41 (C41R1) of Atox1 is relatively high, the only explanation for this is that when spin-labeled Atox1 interacts with MBD1-3 and MBD4-6, the dynamics of C41R1 is reduced, meaning that Atox1 is trapped between the various MBDs. This is in agreement with our previous findings [23], where we suggested that the Atox1 monomer interacts with MBD3-4 only in a face-to-face manner with MBD4, and that it is not affected by the presence of MBD3. Here, the dynamics of the spin-labeled C41R1 position of Atox1 are not affected and not reduced, since there is no other MBD nearby.…”
Section: Probing the Interaction Between The Mbds Of Atp7b And The Mesupporting
confidence: 94%
“…Figure 4 shows the DEER distance distribution functions obtained for the various MBDs in the absence and presence of Atox1. DEER experiments performed on MBD3-4 and MBD3-4_C305A in the presence of sl-Atox1 were already reported by us earlier, and showed a similar broad distance distribution function of between 1.5 and 3.5 nm [23], suggesting that Atox1 interacts only with MBD4, and that no conformational changes in MBD3 occurred while interacting with MBD4. MBD4-6, labeled at C358R1, C431R1 from MBD4, and C490R1 from MBD5 showed three distance distribution functions.…”
Section: Probing the Interaction Between The Mbds Of Atp7b And The Mesupporting
confidence: 78%
See 3 more Smart Citations